Decision-making in the human development bond in Ecuador - Meza Cisneros, Josueth Alfonso (SATHIRI, 2024)
In this article, the decision-making process and ethical dimension in the implementation of conditional cash transfer programs in Latin America are analyzed, with a particular focus on Ecuador’s Human DevelopmentBonus (BDH), the largest program of its kind in the region. These programs have a short-term strategy to alleviate poverty through cash transfers and a long-term strategy to promote investment in human capital through conditions related to health and education, as well as fostering entrepreneurship through BDH advances. The decision making process in the implementation of these programs is influenced by leadership theories such as transformational, situational, charismatic, and transactional leadership, taking into account psychosocial factors and the importance of leaders in the success or failure of these policies. Although there are impact assessment reports in countries such as Mexico, Colombia, and Brazil that analyze similar outcomes, the lack of analysis on decision-making and ethics in these programs is emphasized. In summary, this article provides a comparative analysis of decision-making and ethics in conditional cash transfer programs, with a focus on Ecuador’s BDH, within the context of Latin America.
Keywords: conditional cash transfers; poverty; decision-making; ethics; leadership; social programs; Latin America